Genetic diversity of Coffea arabica L. mitochondrial genomes caused by repeat- mediated recombination and RNA editing - Ni, Yang; Zhang, Xinyi; Li, Jingling; Lu, Qianqi; Chen, Haimei; Ma, Binxin; Liu, Chang (Frontiers in Plant Science, 2023)
Background: Coffea arabica L. is one of the most important crops widely cultivated in 70 countries across Asia, Africa, and Latin America. Mitochondria are essential organelles that play critical roles in cellular respiration, metabolism, and differentiation. C. arabica's nuclear and chloroplast genomes have been reported. However, its mitochondrial genome remained unreported. Here, we intended to sequence and characterize its mitochondrial genome to maximize the potential of its genomes for evolutionary studies, molecular breeding, and molecular marker developments. Results: We sequenced the total DNA of C. arabica using Illumina and Nanopore platforms. We then assembled the mitochondrial genome with a hybrid strategy using Unicycler software. We found that the mitochondrial genome comprised two circular chromosomes with lengths of 867,678 bp and 153,529 bp, encoding 40 proteincoding genes, 26 tRNA genes, and three rRNA genes. We also detected 270 Simple Sequence Repeats and 34 tandem repeats in the mitochondrial genome. We found 515 high-scoring sequence pairs (HSPs) for a self-to-self similarity comparison using BLASTn. Three HSPs were found to mediate recombination by the mapping of long reads. Furthermore, we predicted 472 using deep-mt with the convolutional neural network model. Then we randomly validated 90 RNA editing events by PCR amplification and Sanger sequencing, with the majority being non-synonymous substitutions and only three being synonymous substitutions. These findings provide valuable insights into the genetic characteristics of the C. arabica mitochondrial genome, which can be helpful for future study on coffee breeding and mitochondrial genome evolution.Our study sheds new light on the evolution of C. arabica organelle genomes and their potential use in genetic breeding, providing valuable data for developing molecular markers that can improve crop productivity and quality. Furthermore, the discovery of RNA editing events in the mitochondrial genome of C. arabica offers insights into the regulation of gene expression in this species, contributing to a better understanding of coffee genetics and evolution.